Determinants of Low Birth Weight Among Infants Delivered in Tokora Health Centre IV, Nakapiripirit District - Sunta Joy Ngiro (Uganda Christian University, 2024)
WHO estimated that about 30 million low birth weight babies are born each year (23.4%) (WHO 2016). Ministry of Health estimated about 14.7% prevalence of low birth weight in Uganda in 2020. Tokora HCIV between 2020 and 2021 had a prevalence of 23.1% (Maternity and child Health Department, 2021). The broad objective was to identify the determinants of low birth weight among infants delivered in Tokora HC IV, Nakapiripirit District. A descriptive cross-sectional study was conducted, and data was collected at a point in time and the determinants of low birth weight and its factors were described. quantitative and qualitative methods of data collection were employed. Target participants were mothers who delivered live born babies from Tokora Health centre IV and attended post-natal care within the 6 weeks’ period after delivery. Findings revealed a low birth weight prevalence of 29.4% among babies who were delivered in Tokora Health centre IV, Nakapiripirit District, higher than the 23.1% in between 2020 and 2021 and also 14.7% for MOH, 2020. Significant findings were observed from the gestational age, maternal education and financial support from spouses. The health facility should focus on Health Systems strengthening and improve the capacity to deliver an integrated package on maternal, neonatal and child health service.
Undergraduate research